2017
DOI: 10.3847/1538-4357/aa80dd
|View full text |Cite
|
Sign up to set email alerts
|

A New Signal Model for Axion Cavity Searches from N-body Simulations

Abstract: Signal estimates for direct axion dark matter searches have used the isothermal sphere halo model for the last several decades. While insightful, the isothermal model does not capture effects from a halo's infall history nor the influence of baryonic matter, which has been shown to significantly influence a halo's inner structure. The high resolution of cavity axion detectors can make use of modern cosmological structure-formation simulations, which begin from realistic initial conditions, incorporate a wide r… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
30
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 47 publications
2
30
0
Order By: Relevance
“…For example, the effects of triaxiality, velocity anisotropy and dark substructures have all received attention in the context of direct DM detection before [4][5][6][7][8][9][54][55][56][57][58][59][60][61][62]. Furthermore, recent analyses using hydrodynamic simulations and astrometric data have suggested that the DM halo may be colder than assumed here [63][64][65][66][67]. Here we merely remark that if this is the case then this would emphasise the presence of S1.…”
Section: Models Of the Halo And S1 Streammentioning
confidence: 83%
“…For example, the effects of triaxiality, velocity anisotropy and dark substructures have all received attention in the context of direct DM detection before [4][5][6][7][8][9][54][55][56][57][58][59][60][61][62]. Furthermore, recent analyses using hydrodynamic simulations and astrometric data have suggested that the DM halo may be colder than assumed here [63][64][65][66][67]. Here we merely remark that if this is the case then this would emphasise the presence of S1.…”
Section: Models Of the Halo And S1 Streammentioning
confidence: 83%
“…In the inner halo (where the Sun is located), the distribution of DM particles extrapolated via sub-grid methods in high resolution dissipationless simulations like Aquarius is rather smooth [57], so a smooth velocity distribution is a good assumption. Furthermore, recent hydrodynamic simulations [58][59][60][61] have recovered speed distributions for DM that are better approximated by Maxwellian-distributions than their earlier N-body counterparts [3,[6][7][8][9]62]. In this light, the assumption in the SHM of a Gaussian velocity distribution is surprisingly accurate.…”
Section: The Shm: a Critical Discussionmentioning
confidence: 96%
“…Our data-driven work is complementary to the approach adopted in Refs. [58][59][60][61]. Here, simulated halos built up from successive merger events are examined to extract better motivated velocity distributions than the SHM ansatz.…”
Section: B Simulationsmentioning
confidence: 99%
“…However, after the formation of the Milky Way, it develops a slight stochastic decoherence due to the gravitational clustering effect. The typical velocity dispersion of the ALP dark matter is σ v ∼ 10 −3 c [40], corresponding to a coherence length of λ coh ≈ λ a × 10 3 with λ a = 2π/m a being its Compton wavelength. In our work, we consider an ALP-neutrino interacting Lagrangian which preserves the shift symmetry as…”
Section: Introductionmentioning
confidence: 99%